Gut Microbial Diversity in Female Patients With Invasive Mole and Choriocarcinoma and Its Differences Versus Healthy Controls - Liu, Xiaomei; Pan, Xue; Liu, Hao; Ma, Xiaoxin (Frontiers in Cellular and Infection Microbiology, 2021)
Objective. To investigate variation in gut microbiome in female patients with invasive mole (IM) and choriocarcinoma (CC), and compare it with healthy controls. Methods. Fecal microbiome of 12 female patients with IM, 9 female patients with CC and 24 healthy females were analyzed based 16s rDNA sequencying. Alpha (α) diversity was evaluated using Shannon diversity index and Pielou evenness index, while beta (β) diversity was assessed using principle coordinate analysis (PCoA) of unweighted Unifrac distances. The potential functional changes of microbiomes were predicted using Tax4Fun. The relative abundance of microbial taxa was compared by Welch's t test. The role of varied gut microbiota in IM and CC was analyzed by receiver operating characteristic (ROC) curve. Results. The α diversity and β diversity were significantly different between IM and control, but not between CC and control. In addition, the abundance of cancer-related genes was significantly increased in IM and CC patients. Notably, a total of 19 families and 39 genera were found to have significant differences in bacterial abundance. ROC analysis indicated that Prevotella_7 may be a potential biomarker between IM, CC, and controls. Conclusion. Our study demonstrated that the diversity and composition of gut microbiota in IM patients, CC patients and healthy females were significantly different, which provides rationale for the use of gut microbiota as diagnostic markers and treatment targets, as well as for further study of gut microbiota in gestational trophoblastic neoplasia (GTN).